Metal organic framework loaded heterogeneous iron-based catalyst and application thereof

By supporting Fe active components on metal organic frame materials and using alkylaluminum compounds to promote catalysis, heterogeneous iron catalysts were prepared, which solved the problem of poor thermal stability of traditional homogeneous catalysts and achieved high catalytic activity and thermal stability , suitable for the synthesis of high-performance polyisoprene rubber materials.

CN119192446APending Publication Date: 2024-12-27JINING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411107905.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional homogeneous Fe-based catalysts have poor thermal stability and low catalytic activity, making it difficult to meet the industrial development needs of high-performance polyisoprene rubber materials.

Method used

A heterogeneous iron-based catalyst is prepared by using metal organic frame (MOFs) materials as support, supporting Fe active components, and combining alkyl aluminum compounds as cocatalysts to prepare a heterogeneous iron catalyst for catalyzing isoprene polymerization.

Benefits of technology

The catalyst has achieved high thermal stability and high catalytic activity, with catalytic activity up to 1737.8Kg·P/(mol·Fe·h), which is suitable for the synthesis of high-performance polyisoprene rubber materials and meets the requirements of industrial development.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a metal organic framework loaded heterogeneous iron-based catalyst and application thereof, and belongs to the technical field of heterogeneous catalyst preparation and rubber material synthesis. According to the technical scheme, the catalyst comprises a main catalyst and a cocatalyst, the main catalyst is a Fe active component / MOFs carrier, and the cocatalyst is an organic aluminum compound; the Fe active component is halide of Fe; a traditional small organic molecule carrier (bidentate or tridentate nitrogen-containing compound) is broken through, a solid MOFs material with higher stability serves as a carrier, active components are loaded on the MOFs carrier through post-synthesis metallization, the heterogeneous Fe-based catalyst is prepared, and the catalyst has excellent thermal stability, still has very high catalytic activity at the temperature of 50 DEG C, and can be used as a catalyst for preparing the catalyst. The catalytic activity can reach up to 1737.8 Kg.P / (mol.Fe.h), and the requirements of novel industrial development of polyolefin elastomer materials are better met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heterogeneous catalyst preparation and rubber material synthesis, and specifically relates to a metal organic framework-supported heterogeneous iron-based catalyst and application thereof. Background Art

[0002] As global energy consumption and environmental issues become increasingly prominent, the production and preparation of high-performance polyisoprene rubber materials with high-end materials, green processes and intelligent production have become increasingly important in economic development. The key to achieving the preparation of high-performance rubber materials lies in the design and synthesis of efficient catalysts.

[0003] At present, the catalysts for preparing polyisoprene rubber materials mainly include Ziegler-Natta catalysts, rare earth metal catalysts, and late transition metal catalysts. Among them, iron (Fe)-based catalysts have received increasing attention in the field of catalysis over the past two decades due to their abundant reserves of Fe elements, low prices, green environmental protection, and low toxicity (Organometallics, 2023, 42: 3109-3119; ACS Catal., 2023, 13: 2443-2448; J. Catal., 2023, 426: 234-246). They catalyze the polymerization of isoprene (Ip) to prepare polyisoprene rubber materials with different stereoselectivities, mechanical properties, and application fields. For example, cis-1,4 polyisoprene is an elastomer with excellent elasticity, flexibility and low crystallinity, and is widely used in tires, hoses, adhesives and other fields (Struct. Bond. 2010, 137: 49-108; Journal of Polymer Science, Part A: Polymer Chemistry, 2016, 54 (22): 3609-3615); while trans-1,4 polyisoprene is a crystalline thermoplastic polymer with high wear resistance and tensile strength, and is widely used in golf covers, shape memory materials, medical materials and other fields (Journal of Applied Polymer Science, 2001, 82: 81-89; Tire Industry, 1999, 19(1): 9-13); in addition, 3,4-polyisoprene has excellent anti-skid and low rolling resistance properties because the main chain of the molecule contains side groups, making it an ideal material for the development and preparation of green high-performance tires (Polymer Testing, 2022, 115: 107713; Organometallics, 2009, 28: 4814-4822).

[0004] However, traditional Fe-based catalysts are mainly low-molecular homogeneous catalysts, and the catalyst precursors are mainly composed of bidentate or tridentate aromatic nitrogen-containing compounds complexed with FeCl3 or FeCl2 (Coordin. Chem. Rev., 2019, 390: 127-170; Macromolecules, 2021, 54: 5879-5914; Organometallics, 2023, 42: 3307-3318). During the polymerization process, the active sites are easily affected by environmental factors and decompose and deactivate, resulting in poor thermal stability of the catalyst. The overall catalyst activity is lower than that of other metal catalysts currently used in industry (such as Ti, Co, Ni, rare earth) catalysts, which seriously restricts the industrial development and application of Fe-based catalysts and their high-performance rubber materials.

[0005] Compared with homogeneous catalysts, the active sites of heterogeneous catalysts are highly dispersed and isolated on the surface of solid carriers, so they have better thermal stability, higher catalytic activity, and the advantages of not easy scaling of polymerization kettles and controllable polymer particle morphology, which are more in line with the development requirements of polyolefin industrialization (Angew. Chem. Int. Edit., 2018, 57: 8135-8139; ACS Catal., 2020, 6: 3864-3870; Chem. Rev., 2000, 100: 1347-1376). Therefore, based on heterogeneous catalysts, "breaking" the traditional organic small molecule carriers, using more stable solid carriers, loading the Fe active components on the solid carriers, and obtaining heterogeneous Fe-based catalysts are the key to achieving the preparation of high-activity and high-thermal stability Fe-based catalysts.

[0006] In the past decade, metal-organic frameworks (MOFs) materials have attracted more and more attention from researchers due to their unique porous structure (J.Am.Chem.Soc., 2024, 146:11202-11210; J.Am.Chem.Soc., 2024, 146:13113-13125; J.Am.Chem.Soc., 2024, 146:5715-5734). MOFs are a three-dimensional network material formed by coordination with metal ions or clusters as nodes and organic ligands as connecting chains. They have the characteristics of clear crystal structure, high porosity, ordered pores, and large specific surface area. They are widely used in gas adsorption, separation, storage, drug delivery, chemical sensing and catalysis (ACS Catal., 2024, 14: 9093-9103; Chem. Commun., 2020, 56: 10409-10418; J. Am. Chem. Soc., 2016, 138: 3241-3249). In particular, metal active components can be effectively loaded on the nodes or connecting chains of MOFs through post-synthesis technology to obtain molecular-level solid catalysts. Therefore, MOFs are ideal materials for the development of heterogeneous catalysts. Among them, MOFs (bpy-UiO) containing bipyridine groups on the connecting chain have excellent stability and post-synthetic metallization ability. The heterogeneous catalysts prepared by loading cobalt, palladium and iridium metals have shown great potential application value in CH borylation reaction, hydrogenation reaction and hydrosilylation reaction (J.Am.Chem.Soc.2014,136:6566-6569; J.Am.Chem.Soc., 2015,137:2665-2673; J.Am.Chem.Soc., 2016,138:3241-3249). However, there are very few research reports on the preparation of heterogeneous Fe-based catalysts using MOFs as carriers for the synthesis of polyisoprene rubber materials. Summary of the invention

[0007] The present invention provides a metal organic framework-supported heterogeneous iron-based catalyst and application thereof. The catalyst has excellent thermal stability and high catalytic activity and has broad application prospects in the synthesis of high-efficiency catalysts and high-performance polyolefin elastomer materials.

[0008] The technical solution of the present invention is:

[0009] In the first aspect, a metal organic framework-supported heterogeneous iron-based catalyst is disclosed, including a main catalyst and a co-catalyst, wherein the main catalyst is an Fe active component / MOFs carrier, and the co-catalyst is an organic aluminum compound; the Fe active component is an Fe halide, and the content of the Fe element in the main catalyst is 1 to 3 wt%; the organic aluminum compound is an alkyl aluminum, an alkyl aluminum chloride or an alkyl aluminum hydride.

[0010] Preferably, the halide of Fe is one or two of ferric chloride, ferric chloride, ferric bromide, ferric dibromide and ferric iodide.

[0011] Preferably, the organoaluminum compound is one or two of trimethylaluminum, triethylaluminum, diethylaluminum chloride, diethylaluminum hydride, trihexylaluminum, dihexylaluminum chloride, dihexylaluminum hydride and methylaluminoxane.

[0012] Preferably, the molar ratio of the Fe element in the main catalyst to the Al element in the co-catalyst is 1:30-200.

[0013] Preferably, the preparation method of the main catalyst is: the preparation method of the main catalyst is: under an inert atmosphere, organic solvent, MOFs carrier and Fe active component are added to a reaction bottle in sequence, after stirring the reaction at room temperature, the organic solvent is washed, centrifuged and vacuum dried to obtain the main catalyst.

[0014] Preferably, the organic solvent is one or two of methanol, ethanol, acetonitrile, n-hexane, n-heptane, n-octane, cyclohexane, toluene, chloroform, dichloromethane and xylene.

[0015] Preferably, the preparation method of the MOFs carrier is: in a hydrothermal autoclave, N,N-dimethylacetamide, zirconium chloride and 2,2'-bipyridine-5,5'-dicarboxylic acid are added in sequence, ultrasonicated, stirred to dissolve, trifluoroacetic acid is added, reacted at 90-110°C for 4-6 days, filtered, soaked in dichloromethane, centrifuged, and vacuum dried to obtain the MOFs carrier.

[0016] In the second aspect, the use of the metal organic framework-supported heterogeneous iron-based catalyst in catalyzing the polymerization of isoprene to prepare polyisoprene rubber materials is disclosed. The preparation method of the polyisoprene rubber material is as follows: under an inert atmosphere, one of xylene or toluene, isoprene monomer, a co-catalyst, and a main catalyst are sequentially added into a reaction bottle, the polymerization reaction is stirred at 10 to 50° C. for 5 to 60 minutes, acidified ethanol is added to terminate the reaction, the reaction is washed, and the polyisoprene polymer is obtained.

[0017] Preferably, the molar ratio of isoprene monomer to Fe element in the main catalyst is 1: (0.1-2) × 10 -4 .

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] Traditional homogeneous Fe-based catalysts are easily affected by the polymerization environment, and decompose and deactivate, and have defects such as poor thermal stability and low catalytic activity, which makes it difficult to meet the development requirements of industrialization. On the basis of the existing ones, the present invention breaks through the traditional organic small molecule carrier (bidentate or tridentate nitrogen-containing compounds), uses a more stable solid MOFs material as a carrier, loads the Fe active component on the MOFs carrier, prepares a heterogeneous Fe catalyst, and uses it as the main catalyst. After activation by a co-catalyst, it catalyzes the polymerization of isoprene and synthesizes polyisoprene rubber materials. During the polymerization process, the catalyst exhibits excellent thermal stability and high catalytic activity, and still has very high activity at 50°C. The catalytic activity can be as high as 1737.8Kg·P / (mol·Fe·h), which is more in line with the requirements of the new industrial development of polyolefin elastomer materials.

[0020] The polyisoprene rubber material synthesized by the catalyst and the polymerization process of the present invention has excellent mechanical properties such as elasticity, fatigue resistance, wet skid resistance and low rolling resistance, and is an ideal material for developing green high-performance tires. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0022] The preparation method of the MOFs carrier in the main catalyst is as follows:

[0023] In a polytetrafluoroethylene hydrothermal autoclave, add 200 mL DMF, 403 g 2,2'-bipyridine-5,5'-dicarboxylic acid, and 415 g ZrCl4 in turn, stir at room temperature for 15 min, and ultrasonicate for 15 min. After the sample is dissolved, add 0.8 mL trifluoroacetic acid, react at 100 ° C for 5 days, filter the sample, soak it in CH2Cl2 three times within three days, centrifuge it, and vacuum dry it at 45 ° C for 24 h to obtain a MOFs carrier.

[0024] Preparation of acidified ethanol: Take 98 mL of ethanol, add 2 mL of concentrated hydrochloric acid, mix well, and obtain the acidified ethanol terminator.

[0025] Example 1

[0026] The preparation method of the main catalyst is as follows: under a nitrogen atmosphere, 25 mL of acetonitrile, 2.35 g of MOFs carrier, and 0.54 g of FeCl3 are added to a reaction bottle in sequence, stirred with a magnetic stirrer at room temperature for 24 hours, washed with acetonitrile three times, centrifuged, and vacuum dried at 45°C to obtain a powdered main catalyst MOFs-FeCl3. The Fe content in the main catalyst MOFs-FeCl3 is 2.69 wt% as analyzed by inductively coupled plasma emission spectrometry.

[0027] The preparation method of polyisoprene polymer is as follows:

[0028] A 100 mL round-bottom flask (containing a magnet) was evacuated and replaced with nitrogen three times in sequence. Under a nitrogen atmosphere, 13.29 g of isoprene, 31 g of anhydrous xylene, 0.98 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1), and 0.0405 g of the main catalyst MOFs-FeCl3 were added. The reaction was carried out at 30 ° C for 15 min, and the reaction was terminated by acidified ethanol. The reaction was washed and dried in vacuo at 45 ° C for 24 h to obtain 5.74 g of polyisoprene polymer. The catalytic activity of the catalyst was calculated to be 1177.8 Kg·P / (mol·Fe·h). The polymer contained 41.6 mol% of cis-1,4-polyisoprene structure and 58.4 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0029] Comparative Example 1

[0030] Different from Example 1, in this comparative example, "react at 30° C. for 15 min" was replaced by "react at 5° C. for 15 min", and 1.79 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 367.0 Kg·P / (mol·Fe·h). The polymer contained 41.2 mol% of cis-1,4-polyisoprene structure and 58.8 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and hydrogen nuclear magnetic resonance spectrometer.

[0031] Example 2

[0032] Different from Example 1, in this comparative example, "react at 30° C. for 15 min" was replaced by "react at 50° C. for 15 min", and 6.52 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 1336.8 Kg·P / (mol·Fe·h). The polymer contained 40.8 mol% of cis-1,4-polyisoprene structure and 59.2 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0033] By comparing Examples 1-2 and Comparative Example 1, it can be seen that in the polymerization of isoprene catalyzed by MOFs-FeCl3 as the main catalyst, the reaction temperature affects the catalytic activity of the catalyst. At 30°C and 50°C, the catalytic activity of the catalyst is high, and the higher the reaction temperature, the higher the monomer coordination and chain growth rate, and the better the catalytic activity. At 5°C, the catalytic activity is very low relative to that of Examples 1-2. At the same time, when the polymerization temperature rises to a high temperature of 50°C, the catalytic activity is still very high, and there is no attenuation phenomenon, indicating that the catalyst has excellent thermal stability.

[0034] Example 3

[0035] Different from Example 1, in this comparative example, "0.98 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "1.96 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 100:1)", and 8.41 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 1724.1 Kg·P / (mol·Fe·h). The polymer contained 38.5 mol% of cis-1,4-polyisoprene structure and 61.5 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0036] Comparative Example 2

[0037] Different from Example 1, in this comparative example, "0.98 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "0.89 mL of triisobutylaluminum (concentration of 1.1 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)", and 1.17 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 241.1 Kg·P / (mol·Fe·h). The polymer contained 46.8 mol% of cis-1,4-polyisoprene structure and 53.2 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0038] Comparative Example 3

[0039] Different from Example 1, in this comparative example, "0.98 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "1.96 mL of trioctylaluminum (concentration of 0.5 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)", and 0.29 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 58.1 Kg·P / (mol·Fe·h). The polymer contained 54.4 mol% of cis-1,4-polyisoprene structure and 45.6 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0040] By comparing Example 1, Example 3 and Comparative Examples 2-3, it can be seen that in the case of MOFs-FeCl3 as the main catalyst for catalyzing the polymerization of isoprene, changes in the concentration and type of the co-catalyst will affect the catalytic activity of the catalyst. When the concentration of alkyl aluminum increases from "AlEt3 / Fe=50mol / mol" to "AlEt3 / Fe=100mol / mol", the catalytic activity increases. Triethyl aluminum has the highest catalytic activity, while triisobutyl aluminum and trioctyl aluminum have lower activities. The alkyl aluminum co-catalyst contacts the main catalyst and forms low-valent active centers through a series of alkylation and reduction reactions. The concentration of alkyl aluminum increases, the number of active centers formed increases, and the catalytic activity increases. The smaller the size of the alkyl aluminum molecule (triethyl aluminum < triisobutyl aluminum < trioctyl aluminum), the smaller the steric hindrance, the easier it is to contact the main catalyst, the more active centers are formed, and the higher the activity of the catalyst.

[0041] Example 4

[0042] The preparation method of the main catalyst is as follows:

[0043] Under nitrogen atmosphere, 15 mL of acetonitrile, 10 mL of methanol, 2.35 g of MOFs carrier, and 0.42 g of FeCl2 were added to the reaction bottle in sequence, stirred with a magnetic stirrer at room temperature for 24 h, washed three times with acetonitrile, centrifuged, and dried in vacuum at 45 ° C to obtain the powdered main catalyst MOFs-FeCl2. The Fe content in the catalyst was 2.75 wt% as analyzed by inductively coupled plasma emission spectrometry.

[0044] The preparation method of polyisoprene polymer is as follows:

[0045] A 100 mL round-bottom flask (containing a magnet) was evacuated and replaced with nitrogen three times in sequence. Under a nitrogen atmosphere, 12.54 g of isoprene, 29.26 g of xylene, 0.92 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1), and 0.0374 g of main catalyst MOFs-FeCl2 were added. The reaction was carried out at 30 ° C for 15 min, and the reaction was terminated by acidified ethanol. The reaction was washed and dried at 45 ° C for 24 h in vacuum to obtain 2.36 g of polyisoprene polymer. The catalytic activity of the catalyst was calculated to be 512.0 Kg·P / (mol·Fe~h). The polymer contained 40.6 mol% of cis-1,4-polyisoprene structure and 59.4 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0046] Comparative Example 4

[0047] Different from Example 4, in this comparative example, "react at 30°C for 15 min" was replaced by "react at 5°C for 15 min", and 1.78 g of polyisoprene polymer was obtained, and 0.68 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 148.8 Kg~P / (mol~Fe~h). The polymer contained 42.4 mol% of cis-1,4-polyisoprene structure content and 57.6 mol% of 3,4-polyisoprene structure through Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0048] Example 5

[0049] Different from Example 4, in this comparative example, "react at 30°C for 15 min" was replaced by "react at 50°C for 15 min", and 3.15 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 685.3 Kg·P / (mol·Fe·h). The polymer contained 42.2 mol% of cis-1,4-polyisoprene structure and 57.8 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and hydrogen nuclear magnetic resonance spectrometer.

[0050] By comparing Examples 4-5 and Comparative Example 4, it can be seen that in the polymerization of isoprene catalyzed by MOFs-FeCl2 catalyst, the catalytic activity of the catalyst is high at 30°C and 50°C, and the higher the reaction temperature, the higher the monomer coordination and chain growth rate, and the better the catalytic activity. At 5°C, the catalytic activity is very low relative to Examples 4-5. At the same time, when the polymerization temperature rises to a high temperature of 50°C, the catalytic activity is still very high, and there is no attenuation phenomenon, indicating that the catalyst has excellent thermal stability.

[0051] Example 6

[0052] Different from Example 4, in this comparative example, "0.92 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "1.84 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 100:1)", and 2.29 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 497.8 Kg·P / (mol·Fe·h). The polymer contained 40.6 mol% of cis-1,4-polyisoprene structure and 59.4 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0053] Comparative Example 5

[0054] Different from Example 4, in this comparative example, "0.92 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "0.84 mL of triisobutylaluminum (concentration of 1.1 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)", and 0.67 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 145.2 Kg·P / (mol·Fe·h). The polymer contained 48.1 mol% of cis-1,4-polyisoprene structure and 51.9 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0055] Comparative Example 6

[0056] Different from Example 4, in this comparative example, "0.92 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "1.84 mL of trioctylaluminum (concentration of 0.5 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)", and 0.25 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 54.6 Kg·P / (mol·Fe·h). The polymer contained 46.5 mol% of cis-1,4-polyisoprene structure and 53.5 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0057] By comparing Example 4, Example 6 and Comparative Examples 5-6, it can be seen that in the MOFs-FeCl2 catalyst catalyzing the polymerization of isoprene, the change in the concentration and type of the co-catalyst will affect the catalytic activity of the catalyst. When the concentration of alkyl aluminum increases from "AlEt3 / Fe=50mol / mol" to "AlEt3 / Fe=100mol / mol", the catalytic activity decreases slightly. Triethyl aluminum has the highest catalytic activity, and triisobutyl aluminum and trioctyl aluminum have low activities. The alkyl aluminum co-catalyst contacts with the main catalyst and forms a low-valent active center through a series of alkylation and reduction reactions. The increase in the concentration of alkyl aluminum leads to excessive reduction of MOFs-FeCl2 and reduced catalytic activity. The smaller the size of the alkyl aluminum molecule (triethyl aluminum < triisobutyl aluminum < trioctyl aluminum), the smaller the steric hindrance, the easier it is to contact with the main catalyst, the more active centers are formed, and the higher the activity of the catalyst.

[0058] Example 7

[0059] The preparation method of the main catalyst is as follows:

[0060] Under nitrogen atmosphere, 25 mL of acetonitrile, 2.35 g of MOFs carrier, and 1.00 g of FeBr3 were added to the reaction bottle in sequence, stirred with a magnetic stirrer at room temperature for 24 h, washed three times with acetonitrile, centrifuged, and dried in vacuum at 45 ° C to obtain a powdered main catalyst MOFs-FeBr3. The Fe content in the catalyst was 1.96 wt% as analyzed by inductively coupled plasma emission spectrometry.

[0061] The preparation method of polyisoprene polymer is as follows:

[0062] A 100 mL round-bottom flask (containing a magnet) was evacuated and replaced with nitrogen three times in sequence. Under a nitrogen atmosphere, 7.14 g of isoprene, 16.65 g of xylene, 0.52 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1), and 0.0298 g of main catalyst MOFs-FeBr3 were added. The reaction was carried out at 30 ° C for 15 min, and the reaction was terminated by acidified ethanol. The reaction was washed and dried in vacuum at 45 ° C for 24 h to obtain 3.71 g of polyisoprene polymer. The catalytic activity of the catalyst was calculated to be 1418.2 Kg·P / (mol·Fe·h). The polymer contained 40.2 mol% of cis-1,4-polyisoprene structure and 59.8 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0063] Comparative Example 7

[0064] Different from Example 7, in this comparative example, "react at 30°C for 15 min" was replaced by "react at 5°C for 15 min", and 1.48 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 564.1 Kg·P / (mol·Fe·h). The polymer was characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer, and contained 40.7 mol% of cis-1,4-polyisoprene structure and 59.3 mol% of 3,4-polyisoprene structure.

[0065] Example 8

[0066] Different from Example 7, in this comparative example, "react at 30°C for 15 min" was replaced by "react at 50°C for 15 min", and 4.55 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 1737.8 Kg·P / (mol·Fe·h). The polymer contained 40.4 mol% of cis-1,4-polyisoprene structure and 59.6 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and hydrogen nuclear magnetic resonance spectrometer.

[0067] By comparing Examples 7-8 and Comparative Example 7, it can be seen that in the MOF-FeBr3 catalyst-catalyzed isoprene polymerization, the reaction temperature affects the catalytic activity of the catalyst. At 30°C and 50°C, the catalytic activity of the catalyst is very high, and the higher the reaction temperature, the higher the monomer coordination and chain growth rate, and the better the catalytic activity. At 5°C, the catalytic activity is very low relative to Examples 7-8. At the same time, when the polymerization temperature rises to a high temperature of 50°C, the catalytic activity is still very high, and there is no attenuation phenomenon, indicating that the catalyst has excellent thermal stability.

[0068] Example 9

[0069] Different from Example 7, in this comparative example, "0.52 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "1.04 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 100:1)", and 4.44 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 1694.0 Kg·P / (mol·Fe·h). The polymer contained 47.2 mol% of cis-1,4-polyisoprene structure and 52.8 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and hydrogen nuclear magnetic resonance spectrometer.

[0070] Comparative Example 8

[0071] Different from Example 7, in this comparative example, "0.52 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "0.47 mL of triisobutylaluminum (concentration of 1.1 mol / L, solvent of toluene, molar ratio of Al to Fe of 50:1)", and 0.85 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 323.9 Kg·P / (mol·Fe·h). The polymer contained 46.5 mol% of cis-1,4-polyisoprene structure and 53.5 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0072] Comparative Example 9

[0073] Different from Example 7, in this comparative example, "0.52 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "1.04 mL of trioctylaluminum (concentration of 0.5 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)", and 0.19 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 71.3 Kg·P / (mol·Fe·h). The polymer contained 43.0 mol% of cis-1,4-polyisoprene structure and 57.0 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0074] Example 10

[0075] The preparation method of the main catalyst is as follows:

[0076] Under nitrogen atmosphere, 15 mL of acetonitrile, 10 mL of methanol, 2.25 g of MOFs carrier, and 1.00 g of FeI2 were added to the reaction bottle in sequence, stirred with a magnetic stirrer at room temperature for 24 h, washed three times with acetonitrile, centrifuged, and dried in vacuum at 45 ° C to obtain the powdered main catalyst MOFs-FeI2. The Fe content in the catalyst was 1.51 wt% as analyzed by inductively coupled plasma emission spectrometry.

[0077] The preparation method of polyisoprene polymer is as follows:

[0078] A 100 mL round-bottom flask (containing a magnet) was evacuated and replaced with nitrogen for three times in sequence. Under a nitrogen atmosphere, 9.30 g of isoprene, 21.69 g of xylene, 0.68 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1), and 0.0505 g of MOFs-FeI2 were added. The reaction was carried out at 30 ° C for 15 min, and the reaction was terminated by acidified ethanol. The reaction was washed and dried in vacuum at 45 ° C for 24 h to obtain 1.42 g of polyisoprene polymer. The catalytic activity of the catalyst was calculated to be 415.4 Kg·P / (mol·Fe·h). The polymer contained 42.4 mol% of cis-1,4-polyisoprene structure and 57.6 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0079] Comparative Example 10

[0080] Different from Example 10, in this comparative example, "react at 30° C. for 15 min" was replaced by "react at 5° C. for 15 min", and 0.56 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 165.0 Kg·P / (mol·Fe~h). The polymer was characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer, and contained 42.2 mol% of cis-1,4-polyisoprene structure and 57.8 mol% of 3,4-polyisoprene structure.

[0081] Embodiment 11

[0082] Different from Example 10, in this comparative example, "react at 30°C for 15 min" was replaced by "react at 50°C for 15 min", and 2.10 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 615.2 Kg~P / (mol·Fe·h). The polymer was characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer, and contained 42.4 mol% of cis-1,4-polyisoprene structure and 57.6 mol% of 3,4-polyisoprene structure.

[0083] By comparing Examples 10-11 with Comparative Example 10, it can be seen that in the MOFs-FeI2 catalyst-catalyzed isoprene polymerization, the reaction temperature affects the catalytic activity of the catalyst. At 30°C and 50°C, the catalytic activity of the catalyst is high, and the higher the reaction temperature, the higher the monomer coordination and chain growth rate, and the better the catalytic activity. At 5°C, the catalytic activity is very low relative to Examples 10-11. At the same time, when the polymerization temperature rises to a high temperature of 50°C, the catalytic activity is still very high, and there is no attenuation phenomenon, indicating that the catalyst has excellent thermal stability.

[0084] Example 12

[0085] Different from Example 10, in this comparative example, "0.68 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "1.36 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 100:1)", and 2.87 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 839.5 Kg·P / (mol·Fe·h). The polymer contained 40.1 mol% of cis-1,4-polyisoprene structure and 59.9 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0086] Comparative Example 11

[0087] Different from Example 10, in this comparative example, "0.68 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "0.62 mL of triisobutylaluminum (concentration of 1.1 mol / L, solvent of toluene, molar ratio of Al to Fe of 50:1)", and 0.35 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 103.6 Kg·P / (mol·Fe·h). The polymer contained 47.9 mol% of cis-1,4-polyisoprene structure and 52.1 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0088] Comparative Example 12

[0089] Different from Example 10, in this comparative example, "0.68 mL of triethylaluminum (concentration of 1.0 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)" was replaced by "1.36 mL of trioctylaluminum (concentration of 0.5 mol / L, solvent of n-heptane, molar ratio of Al to Fe of 50:1)", and 0.09 g of polyisoprene polymer was obtained. The catalytic activity of the catalyst was calculated to be 25.8 Kg·P / (mol·Fe·h). The polymer contained 46.8 mol% of cis-1,4-polyisoprene structure and 53.2 mol% of 3,4-polyisoprene structure as characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance hydrogen spectrometer.

[0090] By comparing Example 10, Example 12 and Comparative Examples 11-12, it can be seen that in the polymerization of isoprene catalyzed by MOFs-FeI2 catalyst, the change of the concentration and type of the co-catalyst will affect the catalytic activity of the catalyst. When the concentration of alkyl aluminum increases from "AlEt3 / Fe=50mol / mol" to "AlEt3 / Fe=100mol / mol", the catalytic activity increases. Triethyl aluminum has the highest catalytic activity, and triisobutyl aluminum and trioctyl aluminum have lower activities. The alkyl aluminum co-catalyst contacts with the main catalyst and forms low-valent active centers through a series of alkylation and reduction reactions. The concentration of alkyl aluminum increases, the number of active centers formed increases, and the catalytic activity increases. The smaller the size of the alkyl aluminum molecule (triethyl aluminum < triisobutyl aluminum < trioctyl aluminum), the smaller the steric hindrance, the easier it is to contact with the main catalyst, the more active centers are formed, and the higher the activity of the catalyst.

[0091] In summary, the Fe-based catalyst supported by the MOFs carrier prepared in Examples 1-12 of the present invention is used as the main catalyst, and the alkyl aluminum is used as the co-catalyst to catalyze the polymerization of isoprene to synthesize the polyisoprene rubber material. The catalyst exhibits a very high catalytic activity, which can be as high as 1737.8 Kg·P / (mol·Fe·h), which is much higher than the corresponding traditional homogeneous Fe-based catalyst (i.e., bipyridine Fe catalyst, the activity of bipyridine Fe catalyst reported in the literature (Macromolecules, 2023, 56: 4629-4638) is 117 Kg / (mol·Fe·h)), and is also higher than other transition metal catalysts currently used in industry (such as MgCl2-loaded Ti-based catalysts, with an activity of ~3.3 Kg / (mol·Fe·h), Molecular Catalysis, 2019, 471: 1-8); and the relationship between the catalytic activities of the catalysts is FeBr3>FeCl3>FeCl2>FeI2, which indicates that the type of halogen and the initial valence state of Fe affect the electron cloud density and steric hindrance of the active center metal, thereby affecting the catalyst activity. In addition, the catalyst has very good thermal stability. When the reaction temperature increases to 50°C, the polymerization activity does not decay, but the catalytic activity gradually increases. Although the present invention has been described in detail by combining the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A heterogeneous iron-based catalyst supported by a metal organic framework, characterized in that: It includes a main catalyst and a co-catalyst, wherein the main catalyst is an Fe active component / MOFs carrier, and the co-catalyst is an organic aluminum compound; The Fe active component is Fe halide, and the content of Fe element in the main catalyst is 1-3wt%; The organoaluminum compound is an alkylaluminum, an alkylaluminum chloride or an alkylaluminum hydride.

2. The metal organic framework-supported heterogeneous iron-based catalyst according to claim 1, characterized in that: The halide of Fe is one or two of ferric chloride, ferric chloride, ferric bromide, ferric dibromide and ferric iodide.

3. The metal organic framework-supported heterogeneous iron-based catalyst according to claim 1, characterized in that: The organoaluminum compound is one or two of trimethylaluminum, triethylaluminum, diethylaluminum chloride, diethylaluminum hydride, trihexylaluminum, dihexylaluminum chloride, dihexylaluminum hydride and methylaluminoxane.

4. The metal organic framework-supported heterogeneous iron-based catalyst according to claim 1, characterized in that: The molar ratio of the Fe element in the main catalyst to the Al element in the co-catalyst is 1:30-200.

5. The metal organic framework-supported heterogeneous iron-based catalyst according to claim 1, characterized in that: The preparation method of the main catalyst is: under an inert atmosphere, an organic solvent, a MOFs carrier and an Fe active component are sequentially added into a reaction bottle, after stirring the reaction at room temperature, the organic solvent is washed, centrifuged and vacuum dried to obtain the main catalyst.

6. The metal organic framework-supported heterogeneous iron-based catalyst according to claim 5, characterized in that: The organic solvent is one or two of methanol, ethanol, acetonitrile, n-hexane, n-heptane, n-octane, cyclohexane, toluene, chloroform, dichloromethane and xylene.

7. The metal organic framework-supported heterogeneous iron-based catalyst according to claim 5, characterized in that: The preparation method of the MOFs carrier is as follows: in a hydrothermal reactor, N,N-dimethylacetamide, zirconium chloride and 2,2'-bipyridine-5,5'-dicarboxylic acid are added in sequence, ultrasonically and stirred to dissolve, trifluoroacetic acid is added, the reaction is carried out at 90-110° C. for 4-6 days, filtered, soaked in dichloromethane, and vacuum dried to obtain the MOFs carrier.

8. Use of the metal organic framework-supported heterogeneous iron-based catalyst as claimed in claim 1 in catalyzing the polymerization of isoprene to prepare polyisoprene rubber material, characterized in that: The preparation method of the polyisoprene rubber material is as follows: under an inert atmosphere, one of xylene or toluene, isoprene monomer, co-catalyst and main catalyst are added to a reaction bottle in sequence, and the polymerization reaction is stirred at 10-50° C. for 5-60 minutes, and acidified ethanol is added to terminate the reaction, and the reaction is washed and dried to obtain a polyisoprene polymer.

9. Use of the metal organic framework-supported heterogeneous iron-based catalyst as claimed in claim 8 in catalyzing the polymerization of isoprene to prepare polyisoprene rubber material, characterized in that: The molar ratio of isoprene monomer to Fe element in the main catalyst is 1: (0.1-2) × 10 -4 .